Adverse drug reactions and treatment outcome analysis in multidrug resistant tuberculosis patients at a DOTS plus site - Velingker, Anita; Lawande, Durga (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Multidrug resistant tuberculosis (MDR TB) requires treatment with expensive, toxic, anti-tubercular drugs over a longer duration. Adverse drug reaction (ADR) to second line anti tubercular drugs affect compliance and hence treatment outcome. The primary objective of this study was to analyse ADRs and if these resulted in change or permanent suspension of drug. We also analysed treatment outcome, treatment adherence and co morbidities associated with MDR patients. Methods: A retrospective study was carried out at DOTS plus site in department of Pulmonary Medicine, Goa Medical College on registered MDR cases from November 2011 to October 2016. Socio demographic profile, diagnosis, treatment and ADRs were evaluated, ADRs were evaluated for frequency, causative drugs, management aspect and impact on treatment outcome. Results: Out of 201 MDR cases, 99 cases had 167 ADRs. Majority of patients having ADRs were in age group of 30-50 years with mean±standard deviation 36.82±14.47, 59 (59.59%) males and 40 (40.40%) females, 92 (92.92%) retreatment cases and 7 (7.07%) newly diagnosed. Majority of ADRs were vomiting 31(18.56%), joint pain 31 (18.56%), gastritis 21 (12.57%), hearing impairment 16 (9.58%), numbness in leg 14 (8.38%), depression 12 (7.18%). Treatment outcome of cases with ADR was cured 45 (45.45%), treatment completed16 (16.16%), progressed to XDR 6 (6.06%), transferred out 5 (5.05%), defaulter 14 (14.14%), death 13 (13.13%). Conclusions: It is very important to recognise at the earliest and treat the ADRs with least modification of the treatment regimen to have a good treatment outcome.